Beginning BlackBerry development - Rizk, Anthony (Apress Distributed to the book trade by Springer-Verlag, 2009)
"This book will teach you how to build Java-based BlackBerry applications, starting from the very basics all the way through packaging and distributing, giving you enough knowledge to produce useful, real-world applications." --Publisher's description.